Arteritis of the arms. - Peacock, A; Bunch, C; White, N (1981)
Arteritis affecting the arm vessels occurs in giant-cell arteritis, Takaysu's arteritis syphilis, and Buerger's disease. The lesions are seldom confined to the arms, however, and each condition has a characteristic clinical presentation. We report on a patient with symmetrical arteritis of the arms associated with circulation immune complexes.